Dynamical band gap renormalization in self-organized InAs/GaAs quantum dots - Yuan, Z; Foo, E; Ryan, J; Mowbray, D; Skolnick, MS; Hopkinson, M (Wiley, 2000)
Dynamical hand gap renormalization has been observed in InAs/GaAs self-organized quantum dots using femtosecond time-resolved photoluminescence up-conversion. The energy shift correlates well with the time-dependent dot occupancy, and is independent of the carrier population in the wetting layer or GaAs barriers. These results indicate that the band gap renormalization is due mainly to the Coulomb exchange-correlation interactions among the confined carriers inside the dots.